Strategi Edukasi Media Ular Tangga untuk Meningkatkan Pengetahuan dan Sikap CTPS serta Jajan Sehat Siswa - Nur Aziizah Rihhadattul 'Aisy; Emelia Tonapa; Bernadetha Bernadetha (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
School health can be assessed through indicators of Clean and Healthy Living Behavior, particularly Handwashing with Soap and healthy snack consumption. These indicators are closely related to preventing communicable diseases such as diarrhea. According to the 2020 Indonesian Nutritional Status Survey (SSGI), the incidence of diarrhea in Indonesia reaches 9.8% of the total population, according to the latest estimates. In Samarinda City, diarrhea cases increased from 3,595 in 2021 to 4,981 in 2022, and rose again to 5,352 in 2023. This study adopts a quasi-experimental method with a pretest and posttest design on a single group of participants. As many as 30 fifth-grade students were selected using a simple random sampling procedure. The results showed a significant effect of health education using snakes and ladders media on improving students’ knowledge (p = 0.025) and attitudes (p = 0.000) after the intervention. The snakes and ladders game proved effective in improving students' knowledge and attitudes regarding HWWS and healthy snacks at SDN 003 Sungai Pinang, Samarinda. The results of this study can be utilized as a conceptual foundation by students, educational institutions, and study programs in the development of game-based learning media, as well as a basis for future scientific exploration.